Konsep Dasar Pendidikan Multikultural - Meyniar Albina; Nazwa Afiva (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Multicultural education is an important approach in the context of the diversity of modern society. Multicultural education includes a learning process that respects cultural diversity and seeks to create a deep understanding of the diversity that exists in society. The main aim of this education is to promote equality, tolerance and mutual respect between groups with different ethnic, religious, linguistic and cultural backgrounds. This article discusses the meaning and nature of multicultural education, including an understanding of the importance of diversity, equality and social justice in the learning process. This article also explores how multicultural education can reduce discrimination in society and strengthen social integration.